Prosedur Permohonan Transeksual (Studi Kasus Penetapan No. 15/PDT.P/2015/PN.SMD) - M. Rizky Firdaus; Muhammad Syarif Maula; M. Farid Alfarisi (Jurnal Hukum Respublica, 2018)
The purpose of this study is to explain the procedure for filing an application for an Indonesian citizen who wishes to make a change in the status of the population in terms of sex by way of operation (transsexual) as well as the civil status of the person after the issuance of the application. This type of research uses a normative-empirical research method, using 1 resource person from the Malang City Population and Civil Registry Office and 1 person from the Supreme Court employee at the Kepanjen District Court. The results of the study can be explained by Indonesian law, especially in a civil manner, it is possible to request a sex change, but there is still no legal regulation that concretely deals with transsexuals in Indonesia, which is still a polemic for the community.